2021
DOI: 10.1111/jar.12925
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion of LGBTQ and gender diverse adults with intellectual disability in disability services: A systematic review of the literature

Abstract: Background: Lesbian, gay, bisexual, transgender, queer (LGBTQ) and gender diverse adults with intellectual disability experience exclusion within disability services.Objective: This review explores the experiences of social inclusion/exclusion of this cohort in the context of disability services. Search Method: A systematic search was conducted of peer-reviewed research published between January 2014 and April 2019. Five databases returned 66 articles plus three from hand searches. Appraisal and Synthesis: Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Such limitations in our positionality influenced the interview and focus group questions, as they did not thoroughly address the identity negotiation experiences of those with multiple marginalized identities. For example, individuals with disabilities are often not viewed as sexual beings in society and, therefore, are not included in discussions of LGBTQ+ identity negotiation research (Smith et al, 2021). Future work should more explicitly explore identity negotiation among LGBTQ+ individuals with disabilities or LGBTQ+ people of color to better understand identity negotiation among LGBTQ+ people with multiple marginalized identities.…”
Section: Discussionmentioning
confidence: 99%
“…Such limitations in our positionality influenced the interview and focus group questions, as they did not thoroughly address the identity negotiation experiences of those with multiple marginalized identities. For example, individuals with disabilities are often not viewed as sexual beings in society and, therefore, are not included in discussions of LGBTQ+ identity negotiation research (Smith et al, 2021). Future work should more explicitly explore identity negotiation among LGBTQ+ individuals with disabilities or LGBTQ+ people of color to better understand identity negotiation among LGBTQ+ people with multiple marginalized identities.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research has focused on trans women (Alexander, 2006;McClelland et al, 2012;Newman et al, 2018;Parkes and Hall, 2006;Tu ¨rko glu and Tu ¨rko glu, 2016;Wilson, 2006;Wood and Halder, 2014) and non-binary people with intellectual disabilities (Alexander, 2006;Duke, 2011;Griffiths et al, 2010;McClelland et al, 2012;Newman et al, 2018;Parkes and Hall, 2006;Ramasamy et al, 2017Ramasamy et al, , 2021Smith et al, 2021;Tallentire et al, 2020;Thompson, 2014;Tu ¨rko glu and Tu ¨rko glu, 2016;Wilson, 2006;Wood and Halder, 2014;Wylie et al, 2014) and there is a marked lack of representation of trans men.…”
Section: Lack Of Clear Identitymentioning
confidence: 99%
“…By not identifying characteristics and comments made by trans participants, authors reduce the risk that they will be identified by people around them. Smith et al (2021) identified that the experiences of transgender people are missing from the available literature on LGBTQþ identity, claiming that this may be due to difficulties with recruitment due to marginalisation and lack of visibility within society in general. However, the evidence in the previous sections and the experiences of Jennifer and Ms A as out trans women accessing disability services, suggests that lack of support for this population may have resulted in "fewer people with intellectual disabilities affirming their gender than there may otherwise be" (Smith et al, 2021, p. 1).…”
Section: Studies Examining the Experiences Ofmentioning
confidence: 99%
“…T here are calls for more research into the experiences of transgender people with intellectual disabilities to address a paucity of literature on this group (Smith et al, 2021;Newman et al, 2018;Dinwoodie et al, 2020). "Transgender" (henceforth trans) refers to "people who move away from the gender they were assigned at birth, people who cross over [.…”
mentioning
confidence: 99%
See 1 more Smart Citation